FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH: GOVERNMENT SIZE SEBAGAI MODERASI - Elga Desfianty (2022)
This research is a quantitative study conducted to test and prove the relationship between the influence of local original income, BPK's audit opinion and regional wealth level on the financial performance of local governments moderated by government size. This research focuses on district/city governments in Indonesia in the 2020 period. The samples in the study were 480 data samples selected using the purposive sampling method. The analysis technique used in the study was path analysis with SmartPLS 3.3.3 software and a significance level of 5%. Analysis of research data was carried out using Structural Equation Modeling (SEM). The results of the study found that: 1) local income affects the financial performance of local governments; 2) BPK's audit opinion has no effect on the financial performance of local governments; 3) the level of regional wealth affects the financial performance of local governments; 4) government size does not moderate the relationship of local revenues to the financial performance of local governments; 5) government size does not moderate the relationship of BPK's audit opinions to the financial performance of local governments; 6) government size does not moderate the relationship of local wealth levels to the financial performance of local governments.